Na primeira Terra todos eram Mbya: cotidiano na aldeia entre muitos "tipos de gente" - Ferreira, Luisa Maria (2018)
This research has as its theme the relations between the Guarani Mbya of the Ribeirão Silveira Indigenous Land and other “kind of people”, a category of thought adopted by me, which has awakened my reflection on the meanings attributed by the Mbya, that is: animals, plants, places, dead, beings and “owners”. From living together in this community, at the foot of Serra do Mar, on the north coast of São Paulo, I intend to demonstrate in this ethnography, the importance given by the Guarani Mbya to other “kind of people”. My aim is to find out to what extent their existenice in tekoa is necessary to promote and ensure the teko porã (“good life”) they desire. That is, this work is the search to find the Guarani Mbya questions, guided by the questions they ask themselves, containing the problems they face. Such questions drive and motivate their daily actions and are present in the processes of reflection and knowledge that the Guarani have, as much as we researchers or not, Westerners or not. What can we learn about people from the questions they ask themselves about their way of life? What about the life forms that surround them? The Guarani-Mbya belong to a subgroup of the Guarani people. Speakers of Mbya Guarani, a Guarani language belonging to the Tupi-Guarani family of the Tupi trunk. They are located in the densest and oldest region of non-indigenous occupation in the country. Present according to data from the Centro de Trabalho Indigenista (CTI) in more than a hundred villages in the South and Southeast of Brazil (São Paulo, Rio de Janeiro, Espírito Santo, Paraná, Santa Catarina and Rio Grande do Sul). They are also present in the states of Pará and Tocantins, in addition to Bolivia, Argentina, Paraguay and Uruguay. With regard to language, Mbya Guarani and Nhandeva speakers live in the Ribeirão Silveira TI. A good part of the population is married or descends from marriages between members of both Guarani subgroups, as I was able to ascertain. For the development of this work, a bibliographical study was made on this people. To this was associated the author's coexistence, for eight months, in the tribe as a way of reporting and observing their daily lives and all the questions raised by me, presented above. The research consists of a case study, containing reports and transcripts.